Editorial - Sadílková, Helena; Viková, Lada (Romano džaniben, 2024)
The text presents the second part of two monothematic issues devoted to various forms of Roma efforts to achieve equal status in society, improve living conditions, and ensure that Roma are accepted by the non-Roma public as part of society as a whole. Most of the texts included in this second issue present various forms of these efforts in Slovakia.